2002
DOI: 10.1080/02652040110065422
|View full text |Cite
|
Sign up to set email alerts
|

Crosslinked chitosan microspheres for encapsulation of diclofenac sodium: effect of crosslinking agent

Abstract: For many decades treatment of an acute disease or a chronic illness has been mostly accomplished by delivery of drugs to patients using various pharmaceutical dosage forms including tablets, capsules, pills, suppositories, creams, ointment, liquids, aerosols and injectables as drug delivery systems are the primary pharmaceutical products commonly seen in the market. In the past two and a half decades several advancements has been made in the pharmaceutical products. They have resulted in the development of new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
99
0
7

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(116 citation statements)
references
References 9 publications
7
99
0
7
Order By: Relevance
“…The release of the active agent from the matrix involves initial swelling followed by diffusion of the drug. In all the methods of crosslinking the drug release decreases with increased crosslinking [16] .…”
Section: In Vitrmentioning
confidence: 99%
See 2 more Smart Citations
“…The release of the active agent from the matrix involves initial swelling followed by diffusion of the drug. In all the methods of crosslinking the drug release decreases with increased crosslinking [16] .…”
Section: In Vitrmentioning
confidence: 99%
“…glutaraldehyde, sulfuric acid and heat treatment [16] . Shu and Zhu [21] , Açikgöz et al [22] and Ko et al [23] reported the use of complexation between polyanion tripolyphosphate and cationic chitosan by electrostatic forces resulting in a more homogeneous structure due to the more homogeneous crosslinking process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 4 Broad bands at 3340-3400 cm -1 was assigned to O-H stretching vibration. Characteristic absorbance bands at ~940 and ~1116 cm -1 are associated with saccharine while strong bands at ~1737 and 1651 cm -1 are associated with amide and amine functionalities respectively for pure chitosan [22,23]. found, a broad absorption band of -OH in the range of 3421-3443 cm -1 appeared in the spectrum of crosslinked Chitosan/PVA by Glutaraldehyde.…”
Section: Temparature (C°)mentioning
confidence: 98%
“…Agentes reticulantes, tais como glutaraldeído, etilenoglicol diglicidil éter, tripolifosfato, ácido sulfúrico e epicloridrina, são usados para aumentar a sua estabilidade química e a resistência mecânica. [9][10][11][12][13][14] A alta hidrofilicidade da quitosana, devida ao grande número de grupos hidroxila e grupos amino presentes na cadeia polimérica, permite sua utilização como biomaterial na forma de micropartículas, gel e membrana em diversas aplicações, como veículo de liberação de fármacos, bandagens, géis injetáveis, membranas periodontais etc. 15 A presença de uma alta porcentagem de grupos amino reativos distribuídos na matriz polimérica permite inúmeras modificações químicas, tais como imobilização de agentes quelantes, quaternização, carboxilação, acilação, sulfonação, amidação, formação de complexo polieletrolítico etc.…”
Section: Introductionunclassified